KELAYAKAN USAHA WARUNG HIDUP DALAM RUANGAN UNTUK IBU RUMAH TANGGA PERKOTAAN - Herijanto, Pudji; Fiernaningsih, Nilawati (BISMA: Jurnal Bisnis dan Manajemen, 2020)
The purpose of this study is to describe the potential of the urban housewives to run an in-house nurseries business. Applying a survey method, the sample of this study consisted of 54 respondents. Data were collected by distributing questionnaires to the research respondents and then analyzed by descriptive statistics. The results showed that the urban housewives had the potential to run an in-house nurseries business that focused on seven aspects, i.e., the aspects of marketing, technical, financial, organizational & human resources, law, environment, and social & economy. However, they should mainly focus on the technical aspect of the business. This research is still in the phase of the conceptual study. Therefore, future studies should explore the practical study approach so that the proposed business model of the in-house nurseries can be applied by the urban housewives. Keywords : business aspects, in-house nurseries, urban housewives